From taxation to fighting for the nation: Historical fiscal capacity and military draft evasion during WWI - Luca Bagnato (University of Zurich, Department of Economics, 2022)
Do strong states affect the culture and actions of their citizens in a persistent way? And if so, can the capacity to tax, by itself, have a role in driving this effect? I study how the historical capacity of a state to collect taxes affects the decision of citizens to evade the mandatory military draft. I look at Italy during World War I and identify quasi-exogenous variation in tax collection induced by the administrative structure of Piedmont during the 1814-1870 period. Using newly collected and digitised individual data on nearly all the men of the 1899 cohort drafted in the province of Turin, I find that citizens born in towns with lower historical fiscal capacity are more likely to evade the military draft, and that the effect transmits through changes in culture. Results are consistent with fiscal capacity spurring norms of rule-following able to persist in the long run. Placebo estimates from other Italian territories confirm that the effect I estimate can be attributed to fiscal capacity, and it is not confounded by legal capacity.
Keywords: D73; D74; D91; H20; N43; 330; Fiscal capacity; Tax collection; Culture; Military draft; Italy; World War I